DEVELOPING EFFECTIVE STRATEGIES FOR IMPLEMENTING COMMUNINITY BIBLE STUDY IN CHURCHES OF MASINDI ARCHDEACONARY, MASINDI KITARA DIOCESE - TIINA GODWIN (UGANDA CHRISTIAN UNIVERSITY, 2024)
This research study was conducted based on the topic Discovering effective strategies of implementing Community Bible Study in Masindi Archdeaconry Masindi Kitara Diocese and the purpose of the study was to create a nurturing environment where church and community members could come together in fellowship ,support one another and build a meaningful relationships centered around the study of the Bible leading to personal growth, spiritual maturity and transformation in attitudes, behaviors and character. The objectives of this study were; to analyze the benefits of having Community Bible Study in the churches and communities of Masindi Archdeaconry, to identify the challenges encountered during the process of conducting Community Bible Study in the churches and communities of Masindi Archdeaconry and to investigate the effective strategies that can be used to implement community Bible Study in Masindi Archdeaconry. A case study design using a sample of 60 respondents was adopted. Simple random sampling and purposive sampling techniques were used to select the respondents and data was collected using well designed structured questionnaire and interview guide. The respondents gave the benefits of community of community Bible Study as follows; promotes Spiritual growth and strengthen one‟s faith, promotes discipleship, and said financial constraints. The respondents gave the effective strategies to be used to implement Community Bible Study in Masindi Archdeaconry as; the need for offering trainings and seminars and for Community Bible Study for both leaders and all people , the need for church leaders to encourage people start and conduct Community Bible study from homes, schools and, churches , need for leaders to provide adequate Bible Study materials , need for church leaders to strengthen both Children and Youth and Adult Community Bible Studies . the recommendations of the study indicated that Community Bible study is existing in some churches and schools of Masindi Archdeaconry but there was great need for religious leaders, and coordinators in different churches to put in more effort in teaching, and encouraging their church members to join both children and youth and adults Community Bible Study ministries xi and also encouraging some churches and Sunday schools to start this program especially still without it.
UNDERGRADUATE RESEARCH